Allogeneic stem cell transplantation in patients with aggressive primary cutaneous T‐cell lymphoma – a case series of the ADF working group „cutaneous lymphomas". (17th October 2013) - Moritz, Rose K. C.; Ditschkowski, Markus; Klemke, Claus‐Detlev; Terras, Sarah; Schlaak, Max; Knorr, Martin; Theurich, Sebastian; Hegenbart, Ute; Kremens, Bernhard; Beelen, Dietrich W.; Stücker, Markus; Kreuter, Alexander; et al.
Summary Background Allogeneic stem cell transplantation (alloSCT) is a treatment option for primary cutaneous T‐cell lymphomas that may induce long‐lasting complete remissions. Little information is available on safety and efficacy. Patients and methods We retrospectively reviewed the data from patients with primary cutaneous T‐cell lymphoma treated in the Departments of Dermatology of the Universities of Bochum, Mannheim and Cologne who received subsequent alloSCT between 2005 and 2012. Results Nine patients with aggressive primary cutaneous T‐cell‐lymphoma received alloSCT. With a follow‐up of 14 to 36 months after transplantation, 4 patients are alive and in complete remission. Two patients had recurrent disease post‐transplantation, which was successfully treated with donor lymphocyte infusions. Non‐relapse mortality was observed in three patients in advanced disease stages within six months after alloSCT. One patient showed only partial remission and died of disease after 32 months and one patient died 26 months after alloSCT with cause of death unknown. Conclusions This report documents the possible benefit of a graft‐versus‐lymphoma effect in primary cutaneous T‐cell lymphoma, as has been observed for other T‐cell malignancies and emphasizes that alloSCT warrants further studies in this setting.